2015
DOI: 10.2110/jsr.2015.07
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentology of Ancient Coastal Wetlands: Insights From A Cretaceous Multifaceted Depositional System

Abstract: Coastal wetlands are prominent modern environments widely studied in geomorphology and ecology, but the term ''coastal wetland'' is still barely used for the sedimentological classification of ancient deposits. The depositional system studied here (Leza Formation, Cameros Basin, Early Cretaceous, N Spain) includes diverse carbonate and clastic facies deposited at the sea-land transition, and is an illustrative example of the wide array of sedimentary environments that may occur in coastal wetlands systems. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 108 publications
0
33
0
Order By: Relevance
“…Wilkinson and Drummond, 2004;Suarez-Gonzalez et al, 2015), as it has been reported in numerous modern systems, such as Bahamas (e.g. Bathurst, 1975;Reijmer et al, 2009;Kaczmareck et al, 2010;Harris et al, 2015), Persian Gulf (e.g.…”
Section: Depositional System and Evolution Of The Studied Units In Thmentioning
confidence: 87%
See 1 more Smart Citation
“…Wilkinson and Drummond, 2004;Suarez-Gonzalez et al, 2015), as it has been reported in numerous modern systems, such as Bahamas (e.g. Bathurst, 1975;Reijmer et al, 2009;Kaczmareck et al, 2010;Harris et al, 2015), Persian Gulf (e.g.…”
Section: Depositional System and Evolution Of The Studied Units In Thmentioning
confidence: 87%
“…All these features suggest that sedimentation of the Aldea de Cortés Fm took place in a "coastal wetland" (sensu Suarez-Gonzalez et al, 2015), because it includes numerous sedimentological features that characterize this type of depositional system: shallow-water facies containing both continental and marine fossils, common subaerial exposure, edaphic features, and complex distribution of interbedded continental, transitional, and marine deposits. Mas (1981), Mas and Alonso (1981), and Mas et al (1982) and interpreted the unit, in the study area, as deposited in a lagoon surrounded by a tidal flat environment which, in turn, was surrounded by a fluvial deltaic plain.…”
Section: Depositional System and Evolution Of The Studied Units In Thmentioning
confidence: 99%
“…Finally, the topmost lithofacies is 3) the Usassai-Perdadefogu lithofacies, which alternates carbonates and fine-to middle-grained siliciclastics locally with coal seams. This is typical of a deltaic-mixed lagoon environment ("coastal wetlands" sensu Suárez-González et al, 2015), and suggests the gradual passage to the carbonate shelf of the upper Dorgali Fm (Costamagna and Barca, 2004;Costamagna, , 2015 (Fig. 2).…”
Section: Geological Settingmentioning
confidence: 93%
“…It documents the formation of a main tectonic high later fragmented into several minor highs and culminates with their final transgression. A narrow continental to transitional shallow marine depositional system was formed along the slopes of the tectonic highs (coastal wetland sensu Suárez-González et al 2015). The high-gradient palaeoslopes eroded filling the marginal depositional environments.…”
Section: Genna Selole Formation: Facies Interpretation and Depositionmentioning
confidence: 99%